2020
DOI: 10.1123/jsm.2018-0331
|View full text |Cite
|
Sign up to set email alerts
|

Sexism in Professional Sports: How Women Managers Experience and Survive Sport Organizational Culture

Abstract: Women remain the minority in sport organizations, particularly in leadership roles, and prior work has suggested that sexism may be to blame. This study examines women’s experiences of both overt and subtle sexism in the sport industry as well as the impact such experiences have on their careers. Based on interviews and journal entries from women managers working in a men’s professional sports league, the findings suggest that the culture of sport organizations perpetuates sexism, including the diminishment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 47 publications
3
40
0
1
Order By: Relevance
“…While previous work has been informative on harassment and the subsequent experiences of women in traditional sport (e.g., basketball, hockey: Fasting et al, 2007;Hindman & Walker, 2020;Taylor et al, 2018), this occurrence has not been previously expanded upon in nontraditional sport spaces (i.e., esports). Further, to our knowledge, only a small number of studies within the esports industry have identified the existence of hostility and discrimination for esports participants (e.g., Cameron, 2019;Darvin et al, 2020; J.T.…”
Section: Introductionmentioning
confidence: 99%
“…While previous work has been informative on harassment and the subsequent experiences of women in traditional sport (e.g., basketball, hockey: Fasting et al, 2007;Hindman & Walker, 2020;Taylor et al, 2018), this occurrence has not been previously expanded upon in nontraditional sport spaces (i.e., esports). Further, to our knowledge, only a small number of studies within the esports industry have identified the existence of hostility and discrimination for esports participants (e.g., Cameron, 2019;Darvin et al, 2020; J.T.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by other international sport management research which discusses the role of sport in shaping cultural discourse and processes that drive and facilitate change [ 39 ]. However, the culture of sport still perpetuates sexism including diminishing and objectifying women’s capabilities [ 40 ]. Another example is sexist language towards women and girls which often reinforces the position of men dominating the sporting landscape [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haslam et al, 2020). However, this also presents issues that individuals with certain characteristics (e.g., men) may be more likely to embody the shared response of a sport organization because it is a stereotypically masculinized environment (Hindman & Walker, 2020). However, there is also evidence that organizations that value diversity can embrace this as a feature of shared identity (Rink & Ellemers, 2007), thus indicating that where prototypicality reflects inequalities within a sport organization, the root cause may be social and/or structural, rather than in the deployment of identity leadership.…”
Section: Roles Of Identity Leadership In Crisis Responsementioning
confidence: 99%